The question of unity of Slavic people in the works of Joseph Perwolf - Kijas, Artur (Balcanica Posnaniensia. Acta et studia, 2009)
The article presents the life and scientific activity of the Czech Slavicist Józef (Josyp) Perwolf (1841–1891), one of the most prominent researchers of Slavic studies in the second half of the 19th century, professor at the Imperial University of Warsaw. The starting point is a discussion of the historical and intellectual background of his work – the era of national revival in Bohemia and the development of Pan-Slavic ideas in Central and Eastern Europe. The aim of the research is to analyse Perwolf's views on the idea of Slavic unity, understood by him both as a spiritual and cultural community and as a potential political solidarity of Slavic nations. The study is based on Perwolf's publications in Czech and Russian, as well as archival sources concerning his teaching work in Warsaw. The author of the article uses a historical-comparative analysis method, placing Perwolf's ideas in the context of the Pan-Slavic and Russophile concepts of the time. Perwolf is shown to be a scholar who combined moderate Russophilia with a deep interest in the history and culture of the West and South Slavic nations. Despite their pro-Russian tone, his works were characterised by broad erudition, a critical approach to sources, and a desire to establish the idea of a Slavic community on a scientific basis. A. Kijas emphasises that Perwolf was one of the first Slavicists to attempt to present the idea of Slavic unity in a historical context.